Práticas de objetivação e subjetivação docente: estratégias de saber-poder no contexto do Pibid - Martins, Waléria Andrade (Universidade Federal de São Carlos, 2018)
This work aims to question teacher´s objectivation and subjectivation practices in the context of the Institutional Scholarship Program of Initiation to Teaching (Pibid). In the dissertations and thesis researched about the Program, as well as in the institutional documents, the Pibid has been considered as a way to improve the education quality and to give importance to the teaching profession.The relationships between the school teacher and the university teacher have been modified through the Program. With a Foucauldian regard, this research assumes a discursive perspective, based in terms of a Michel Foucault´s Arche genealogy. The selection of the corpuswas made based on the following regularity: statements that refer to the objectives of the Pibid. These statements were organized into homogeneous series forming series of statements, which appear in the same places of enunciation: i) edicts; ii) academic events; iii) interviews.When we investigate the statements, in a perspective, which considers fundamentally the historical conditions, our regard turns to the teacher´s objectivation and subjectivation practices. Therefore, assuming Pibid as a research field, whose speech is produced by a set of discursive practices on the teaching object, we propose the following problem-question: to what extent can Pibid's practices be considered as a strategic instrument of teacher´s knowledge-power? To answer this question, the analytical chapters of this thesis have the following specific objectives: i) To describe and understand the historical conditions of the emergency of the Pibid and ii) To analyze the processes of objectification and subjectivation of the teacher subject. In this sense, we analyze, in i), how the emergence of the Pibid practices produce or (trans)form the teacher and his subjectivity.We also seek to analyze, in (ii), to what extent the circulating knowledges in the framework of the Program modify the teacher´s subjectivity and in which they modify.From the questioning proposed in this thesis, the analysis allow us to understand that the constitution of the teacher subject reveals the existence of a set of knowledge-power strategies which seek to classify, to formalize, to categorize, and to discipline the teacher through statements which refer to the valorization of the teaching profession, to the education quality and to the university-school integration. Thus, we understand that the Pibid Program has worked as a strategic instrument that operates on the conduct of the teacher's actions, in order to direct and shape the teacher subject according to what is considered positive for the population's security. That is, the achievement of more satisfactory evaluation indexes.
Teacher's objectivation and subjectivation practices: strategies of knowledge-power in the context of Pibid
Keywords: Pibid; Discurso; Saber-poder; Governamentalidade; Subjetivação docente; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL